Virtual Hologram Learning As A Publishing Media Of Nusantara Culture, Study Case: Mabayang-Bayang Tradition In Sengkiding Village - Ni Made Dwi Anggirawati; Ni Luh Putu Agustin Kanya D; Ida Ayu Alit Srilaksmi; Komang Widya Kartika Sari (Sociae Polites, 2022)
Technology has developed and affect so many aspects of people’s lives. The presence of increasingly rapid technology could be an effective medium to be use to distributing information. Virtual Hologram Learning is a technology product that is formed from the combination of two coherent light rays in microscopic form. Virtual Hologram Learning can be used as a medium of information for the people of the archipelago in terms of culture and use to preserve the culture of the archipelago. Bali is an island known as an island that has abundant cultural diversity has a unique cultures called Mebayang-Bayang Tradition from Sengkiding Village, Klungkung. Which is held every Pengrupukan (a day before Nyepi) involves the villagers pulling the cow bones. The method used in this study is a qualitative method which aims to understand the factors that influence the research subject (Sengkiding villager) want to carry out the tradition. The type of data used is primary data sourced from the results of direct observations from the informants who has understanding about this tradition. Furthermore, the data will be published through Virtual Hologram Learning as a form of publishing Nusantara culture. Keyword: Virtual, Hologram, Publishing, Cult